In Vitro α-Amylase and α-Glucosidase Inhibition and Phytochemical Profiling of Methanolic Extract of Leea asiatica - Krishna R. Bhendarkar; Dr. Mohit Shrivastav; Dr. Tulsidas Nimbekar (The Bioscan, 2025)
Background The rise in world cases of type 2 diabetes has made finding secure and natural antidiabetic treatments more important. Although it has many naturally occurring active ingredients, the enzyme-inhibitory effects of Leea asiatica have not often been studied. Objective Assessing the ability of Leea asiatica methanolic leaf extract to block α-amylase and α-glucosidase as in vitro antidiabetic tests and also performing initial screening of phytochemicals. Methods Leea asiatica leaves were Soxhlet-extracted in methanol and screened for various phytochemicals. The extract was assessed for its power to stop α-amylase and α-glucosidase enzymes using well-known colorimetric tests in a test tube. Acarbose was used as the reference drug. The degree of IC₅₀ was measured using dose-response plots to find the strongest inhibitors. Results After analysis, flavonoids, alkaloids, tannins and phenolic compounds were identified. At increasing concentrations of the ex-tract, both α-amylase and α-glucosidase were inhibited. Results indicated that the extract shows similar action to acarbose in controlling blood sugar after a meal. Conclusion Researchers have demonstrated that the rich chemical composition of methanolic leaf extract from Leea asiatica helps it achieve high in vitro inhibition of carbohydrate-hydrolyzing enzymes. Evidence shows that it could be used for antidiabetes in tradi-tional medicine, so more work should be done to determine how it works and to isolate its key components.